Improving the Implementation of the Ultimum Remedium Principle in Law Enforcement against Crimes Committed by Corporations - Tagor Aruan; Yasmirah Mandasari Saragih (Pusat Riset dan Inovasi Nasional, 2024)
This study examines the strengthening of the ultimum remedium principle in handling corporate crimes as part of a more proportional, efficient, and equitable criminal justice system reform. The ultimum remedium principle views criminal law as a last resort, used after other legal mechanisms, such as administrative resolution, mediation, or administrative sanctions, are deemed inadequate. The application of this principle becomes increasingly important in the corporate context to prevent the negative impact of repressive punishment on business entities that play a strategic role in the national economy. The significant impact of corporations on society and the economy necessitates a more careful and prudent approach to handling corporate crimes. This study uses a normative juridical method with statutory, conceptual, and case study approaches. In analyzing the application of the ultimum remedium principle, this study identifies that although this principle has been incorporated into several laws and regulations, its implementation remains weak. Factors contributing to this include limited understanding of the principle among law enforcement officials, suboptimal technical guidelines regarding the application of the ultimum remedium principle, and public pressure that tends to encourage a repressive approach in handling corporate crimes. Therefore, this study recommends strengthening regulations, increasing the capacity of law enforcement officials, and developing integrated guidelines to ensure the consistent and effective application of the ultimum remedium principle in handling corporate crimes. The application of this principle is also in line with the restorative justice approach, which aims to provide more humane and corrective punishment and create sustainable change for corporations and society.